A new method for evaluating stony debris flow rainfall thresholds: the Backward Dynamical Approach. Issue 6 (June 2019) - Rosatti, Giorgio; Zugliani, Daniel; Pirulli, Marina; Martinengo, Marta
Abstract: Debris flow rainfall thresholds aim to provide a level of rainfall duration and average intensity above which the probability of a debris flow occurrence is significant. Estimating reliable thresholds for use in early warning systems has proved to be a challenging task. In fact the methodologies currently available in the literature are not entirely satisfactory since they provide thresholds unlikely low. The goal of the present research is exploring new paths aimed at improving the reliability of rainfall thresholds. A possible weak point of the literature approaches is the way the duration and the average intensity pertaining to a debris flow is determined. Up to now, these values are evaluated using only the characteristics of the hyetograph associated to a debris-flow event. In the present paper, we propose a new methodology based on volumetric relations deriving from a simplified description of the dynamic of a stony debris flow: by using these relations, from a measure of the deposited volume it is possible to estimate backwardly the volume of rain that caused the deposition; then, from this last value and the knowledge of the relevant hyetograph, it is possible to reconstruct the duration and the average intensity. Application of this new technique to a sample study area allowed us to prove the feasibility of the method and, to some extent, its capabilities: with respect to a classical literature method, the new approach produces an higher threshold and a smaller characteristic duration scales. Finally, strengths and weakness of the method have been evaluated thoroughly.